Process of language Use and Development: Case Studies in 6 Years of Age - Mariani, Titin; Harahap, Rosmawati (PT. Riset Press International, 2024)
The aim of this research is to determine the process of first language acquisition and development in 6 year old children. The method used in this research is a qualitative analysis method. The technique used in processing data and obtaining data is through observation and interviews with parents and children directly (face to face). The results of the research show that children's language development goes through several patterns, namely crying, cooing, moaning, intonation patterns, one-word speech, two-word speech, data inflections, interrogative sentences, rare/complex constructions, and mature speech.Furthermore, there are several levels of children's language, namely pre-speech, first words when names appear, word combinations and grammar. Meanwhile, there are several ways for children to acquire language, namely through acquisition and teaching. There are four factors in language acquisition, namely biology, environment, intelligence, and motivation. Parental involvement and supervision also greatly influences the complex process of children's language development.